Shanghai Residents' Cognition, Attitudes and Expressions Towards Significant Political Events -A Case Study of the 2013 "Two Sessions" of China - Zheng Bofei (Asian Journal for Public Opinion Research)
China's "two sessions," namely, the National People's Congress (NPC) and the Chinese People's Political Consultative Conference (CPPCC), has significant meaning to the political life of the nation. It collects opinions and advice from different groups of people annually. "Two sessions" 2013 was especially eye-catching, because new state leaders were elected at the meetings. Using CATI (Computer Assisted Telephone Interviewing) system, the Media and Public Opinion Center of Fudan University (FMORC) conducted surveys of China's "two sessions" every year from 2007 to 2013. In 2013, the influence of new media on public opinion has become increasingly significant. Microblog and WeChat have become two types of important media for Shanghai residents to express their opinions and take part in China's "two sessions." Based on the empirical findings, this paper examines Shanghai Residents' cognition, attitudes and expressions towards "two sessions" 2013 and analyzes how new media affect the public opinions on significant political events.